A Comparative Study of Leaf Litter Decomposition Rates in a Hill Forest and a Forest Plantation in Peninsular Malaysia - See, Lee Su; Koon, Yong Teng (1985)
A comparison of seraya (Shorea curtisii Dyer ex. King) and pine (pinus caribaea var. Hondurensis) leaf litter was made over a period of16 weeks in a Hill Dzpterocarp Forest (HDF) and in a pine plantation (PP). At both sites, seraya leaves decomposed at a faster rate than pine needles. Weight losses after 16 weeks from seraya leaves varied from 19.5% (PP) to 39.0% (HDF) while pine needles showed weight losses varying from 10.3% (PP) to 13.6% (HDF). Soil microarthopods were suspected to playa more important role in seraya leaf litter decomposition in the HDF than in the PP. The significance ofthese findings onforest management is discussed..